A heat-insulating microfiber centrifugal glass wool thermal insulation material and a preparation method thereof
By using a composite material of modified fiber cotton and porous adhesive in centrifugal glass wool, the problem of excessive cross-linking of acrylic adhesives is solved, the material's temperature resistance and sound insulation performance are improved, and the heat insulation effect is enhanced.
Patent Information
- Application Number
- CN202411922362.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The cross-linking degree of acrylic adhesive in existing centrifugal glass wool is too high, blocking the gap of glass fibers, resulting in ineffective weakening of air convection and reducing temperature resistance and sound insulation performance.
Using a composite material of modified fiber cotton and porous adhesive, air convection is promoted by attaching nanotin oxide to the surface of the fiber and adding porous bodies to the adhesive.
It improves the temperature resistance of glass wool, enhances the absorption capacity of sound waves, and maintains good heat insulation.
Smart Images

Figure CN119349925B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermal insulation materials, and in particular to a thermal insulation microfiber centrifugal glass wool thermal insulation material and a preparation method thereof. Background Art
[0002] Glass wool has good thermal insulation properties, fireproof partition properties and excellent sound absorption capabilities, and has been widely used in the construction industry. However, the glass fiber itself has poor bonding strength, and adhesives are often required to bond the glass fibers during the preparation process. The adhesive has a great influence on the performance of the glass wool.
[0003] The main components of glass wool are glass fiber and adhesive, wherein glass fiber is mainly composed of quartz sand, feldspar, dolomite, limestone, borax, soda ash, etc. In order to enhance the performance of glass wool, the existing technology enhances the strength and performance of glass wool by adding various elements to the glass raw materials. However, since the fiber diameter of glass wool is at the micron level, the added metal elements will form crystal nuclei, thereby obtaining ceramic wool. However, ceramic wool is heavier and the construction is not as convenient as glass wool. Therefore, when improving the heat resistance and other properties of glass wool, it is impossible to add too many elements to the raw materials to improve the performance. This is one of the defects of existing glass wool; secondly, the second main component of glass wool is adhesive, in which phenolic resin and other substances such as urea, ammonium sulfate, The combination of special oils, ammonia water and other substances can bond glass wool well, but phenolic resin is prone to cracking after long-term use, and its brittleness makes the connection between glass wool loose and easy to produce debris, which endangers the health of workers; therefore, acrylic resin adhesives have emerged. Due to its large molecular weight, acrylic resin adhesives will block the gaps in the glass wool, causing the compression deformation and thermal insulation properties of the glass wool to deteriorate. This is because the irregular gaps in centrifugal glass wool prevent air convection and weaken the role of convection in heat conduction, which makes the centrifugal glass wool have good thermal insulation and heat insulation effects; therefore, the circulation gaps are reduced, and without the existence of gaps, the material itself occupies more space, which will reduce the thermal insulation performance, and correspondingly other properties are also reduced. Summary of the invention
[0004] In order to solve the problem that the cross-linking degree of acrylic adhesive in centrifugal glass wool is too high, the gap between glass fibers is blocked, the centrifugal glass wool cannot effectively weaken the air convection, and too much acrylic resin transfers energy, resulting in the decrease of the heat resistance and sound insulation performance of the centrifugal glass wool, the present application provides a heat insulating microfiber centrifugal glass wool thermal insulation material, and the specific composition of the thermal insulation material is as follows:
[0005] The thermal insulation material is prepared by compounding 45-60 parts of modified fiber cotton and 40-55 parts of porous adhesive, wherein the modified fiber cotton is prepared by mixing 100-140 parts of ore raw materials and 3-8 parts of calcium fluoride, sintering the mixture, and then soaking the mixture in a modified tin liquid, wherein the modified fiber cotton is produced by a centrifugal blowing method, and the modified tin liquid is prepared by compounding hydrochloric acid, tin, and polydimethylsiloxane;
[0006] The porous adhesive is composed of 20-30 parts by weight of porogen, 60-80 parts by weight of acrylic ester composite emulsion, and 5-10 parts by weight of surfactant. The preparation steps of the porous adhesive are as follows:
[0007] A1, polymerization of the porous skeleton, mixing methyl methacrylate and triallyl isocyanurate, adding a porogen and an initiator to carry out polymerization reaction, and obtaining a porous skeleton;
[0008] A2, formation of a porogen, dispersing p-toluenesulfonyl hydrazide or 4,4-oxobisbenzenesulfonyl hydrazide in an alkaline solution to obtain a fluid, placing a porous skeleton in the fluid and stirring, adding an acid solution to neutralize to neutrality and then standing, filtering to obtain a porogen, and irradiating the porogen with low-temperature plasma to activate the surface of the porogen;
[0009] A3. Then, the porogen in A2 is dispersed in an acrylic ester composite emulsion, and a surfactant is added dropwise to obtain a porous adhesive.
[0010] In order to improve the heat resistance of centrifugal glass wool, the present application firstly uses a modified substance on the fiber surface of the centrifugal glass wool to attach nano tin oxide to the fiber surface of the fiber wool, which not only does not affect the gap between the fiber wool, but also does not form crystal nuclei during the firing process, does not increase the fiber weight, and eliminates the possibility of affecting the glass fiber construction; secondly, the present application uses a porogen and an acrylic ester composite emulsion for compounding, the porogen can release gas during the molding process of the centrifugal glass wool, and is connected to form irregular channels along the porous skeleton, the porogen is composed of a porous skeleton and p-toluenesulfonylhydrazine or 4,4-oxybisbenzenesulfonylhydrazine, the p-toluenesulfonylhydrazine or 4,4-oxybisbenzenesulfonylhydrazine is dissolved by an alkaline solution, and then under the action of flow, is located inside the porous skeleton The part is connected to the outside, and then the acid is neutralized to make p-toluenesulfonyl hydrazide or 4,4-oxybisbenzenesulfonyl hydrazide re-precipitate, so that it is located and attached to the porous skeleton. The porous skeleton after attachment can remain stable in the adhesive system, and after being sprayed on the surface of the glass wool, the subsequent curing and heating operations make p-toluenesulfonyl hydrazide or 4,4-oxybisbenzenesulfonyl hydrazide release gas. The gas is filled between the porous skeletons and forms connected channels inside the porous skeleton. However, it can be seen from the data in the examples of the present application that without the presence of a porous skeleton, p-toluenesulfonyl hydrazide or 4,4-oxybisbenzenesulfonyl hydrazide will only form bubbles in the adhesive system, rather than pore channels connected to the outside world. Therefore, it has no good effect on the adsorption of sound, and has a more important impact on the thermal insulation performance.
[0011] Preferably, the weight ratio of the amount of p-toluenesulfonyl hydrazide or 4,4-oxobisbenzenesulfonyl hydrazide in A2 to the amount of the porous framework is 0.6-1.4:1, the gas used in the low-temperature plasma is NH3, and the irradiation time is 3-5 min.
[0012] In the present application, low-temperature plasma is used to irradiate the porous skeleton. The gas used is NH3, which contains N, N+ and metastable N in the plasma state. It has high activity and can form free radicals on the surface of the material, thereby facilitating connection with the acrylic ester composite emulsion in the subsequent process, thereby increasing the strength of the glass wool insulation material.
[0013] Preferably, the ore raw material consists of 80 parts of quartz sand, 20-40 parts of potassium feldspar, 10-30 parts of dolomite, 5-15 parts of limestone, 30-50 parts of borax, and 1-5 parts of soda ash.
[0014] Preferably, the dispersant in A1 is polyvinyl alcohol, the polymerization temperature is 65-80°C, the polymerization time is 6-12h, and then 0.5BV of ethanol is used for soaking to remove impurities, and then 2BV of ethanol and hydrochloric acid are used for washing at a flow rate of 1BV / h for 2h, and then sodium hydroxide solution is used for alkaline washing, and water is washed until neutral to obtain a porous skeleton.
[0015] Preferably, the acrylic ester composite emulsion consists of methyl methacrylate, butyl acrylate, glycidyl methacrylate, an emulsifier, and a pH adjuster.
[0016] The present application also provides a method for preparing a heat insulating microfiber centrifugal glass wool thermal insulation material, and the specific preparation steps are as follows:
[0017] S1. Mix and grind the ore raw material and calcium fluoride, heat to 1360-1450°C until molten state and keep for 10-20min, perform centrifugal spray coating to obtain glass fiber, soak the cooled glass fiber in modified tin liquid, add ammonia water dropwise until white crystals stop precipitating, let stand, filter and dry, and then place at 520-580°C for 1-6h;
[0018] S2. The porous adhesive is evenly sprayed onto the surface of the modified fiber cotton by air spraying. After the cotton is shaped, it is heated to 230-280° C. for pore formation and curing to obtain a glass wool thermal insulation material.
[0019] In the process of preparing glass fiber, the present application uses calcium fluoride, which can increase the toughness of glass fiber, effectively prevent glass wool from becoming brittle and cracking after long-term use, avoid the generation of fine debris, and increase the fiber hardness and corrosion resistance of micron-level glass wool, effectively extending the service life of glass fiber. In addition, the present application uses modified tin liquid, after impregnating the surface of glass fiber, dripping ammonia water, can form white solid crystals of hydrated tin oxide, and after heat treatment, while further increasing the fiber strength, it will also strengthen the bonding strength between tin oxide and fiber, not only will it not form a crystal nucleus, but it can also form a better match with glass fiber. After the composite modification of tin oxide and glass fiber, the mechanical strength of glass wool is further increased, the thermal insulation of glass wool is improved, and the thermal insulation effect is enhanced. In the glass field, tin oxide can enhance the permeability of glass and make the appearance more outstanding.
[0020] Preferably, the modified tin solution is prepared by a composite configuration of hydrochloric acid, tin and polydimethylsiloxane, the concentration of the hydrochloric acid is 1 mol / L, and the weight ratio of the polydimethylsiloxane to the tin is 2-5:12.
[0021] The hydrochloric acid and tin form tin chloride, and then with the addition of ammonia water, hydrated tin oxide is formed, and the connection with the glass fiber is strengthened under the action of polydimethylsiloxane.
[0022] Preferably, the preparation step of the acrylate composite emulsion is: emulsion polymerization of methyl methacrylate, butyl acrylate and glycidyl methacrylate to obtain the acrylate composite emulsion, the emulsifier is sodium dodecyl sulfate, and the pH regulator is sodium bicarbonate.
[0023] Preferably, the rotation speed of the centrifugal spraying of S1 is 3500-3900 rad / min.
[0024] The preparation method of the heat-insulating microfiber centrifugal glass wool thermal insulation material of the present application can also be used in the preparation of building thermal insulation materials, thereby reducing the quality of the thermal insulation materials while improving the performance of the thermal insulation materials.
[0025] The beneficial effects of the present invention are:
[0026] 1. The present application adds calcium fluoride to the raw materials of glass fiber wool to enhance the toughness and strength of the fiber wool, and then uses an outer tin oxide layer on the outer surface of the fiber wool. The method used is to form a uniform oxide layer on the surface of the glass wool fiber through acid and alkali crystal precipitation, which further enhances the strength of the glass fiber. Therefore, over a long period of use, the brittleness is reduced, the service life is increased, and there are fewer glass fragments.
[0027] 2. The present application adds porogens to the design of the adhesive, so that after the adhesive comes into contact with the glass fiber and is heated and cured, the foaming agent therein can be squeezed along the internal space of the porous skeleton to form interconnected airways rather than single bubbles. The uneven gaps formed can not only produce similar effects to the gaps between the glass fibers, but also the size of the pore channels is uniform and stable, and no bubbles of uneven sizes are generated. Therefore, the glass wool has a stronger absorption of sound wave energy and a stronger ability to weaken air convection, and the resulting thermal insulation material has stronger heat resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The thermal conductivity and tensile strength curves of the embodiments of the present invention and the comparative examples are shown in FIG.
[0029] Figure 2 The figure is a bar graph of the sound absorption coefficients of the embodiments of the present invention and the comparative examples. DETAILED DESCRIPTION
[0030] The following will refer to the attached Figure 1 to Figure 2 The embodiments of the present invention are described in detail. It should be understood by those skilled in the art that these embodiments are only used to explain the technical principles of the present invention and are not intended to limit the protection scope of the present invention.
[0031] Preparation Example 1
[0032] Preparation of porous adhesive
[0033] A1. Methyl methacrylate and triallyl isocyanurate are mixed in a mass ratio of 3:1 to form a polymer component, and then 50% of the mass of the polymer component of petroleum ether as a porogen and 1% of the mass of the polymer component of azobisisobutyronitrile as an initiator are added to the polymer component to obtain an oil phase, polyvinyl alcohol is mixed with water to form a 1% aqueous solution as the water phase, and the oil phase is added dropwise to the water phase, and the volume ratio of the oil phase to the water phase is 1:4, the temperature is raised to 65°C, and the reaction is carried out for 6 hours, and then the temperature is raised to 80°C and the reaction is carried out for 3 hours; 0.5BV of ethanol is used for soaking to remove impurities, and then 2BV of ethanol and hydrochloric acid are used for washing at a flow rate of 1BV / h for 2 hours, and finally sodium hydroxide solution is used for alkali washing, and water is washed until neutral to obtain a porous skeleton;
[0034] A2, formation of a porogen, dispersing p-toluenesulfonyl hydrazide in a sodium hydroxide solution with a mass concentration of 10% to obtain a fluid, the solid-liquid ratio of p-toluenesulfonyl hydrazide to the sodium hydroxide solution is 2.5 g / 100 mL, placing a porous skeleton in the fluid and stirring, the weight ratio of p-toluenesulfonyl hydrazide to the porous skeleton is 1:1, adding hydrochloric acid to neutralize to neutrality and then standing for 2 hours, filtering to obtain a porogen, using low-temperature plasma to irradiate the porogen, using a low-temperature plasma treatment device with a radio frequency of 13.56 MHz and an output power of 300 W to irradiate for 3 minutes, and the gas medium is NH3, so that the surface of the porogen is activated;
[0035] A3, methyl methacrylate, butyl acrylate and glycidyl methacrylate were mixed in a molar ratio of 1:0.8:0.05, and stirred in deionized water to form an emulsion, and then an emulsifier sodium dodecyl sulfate and a pH regulator sodium bicarbonate were added with a molar number of 10% of methyl methacrylate, and ammonium persulfate with a molar number of 1% of methyl methacrylate was added dropwise, and the temperature was raised to 65°C for reaction for 3 hours, and then the temperature was raised to 85°C for standing for 2 hours, and then the pH was adjusted to neutral, and filtered after standing to obtain an acrylate composite emulsion;
[0036] Finally, 25 parts of the surface activated porogen in A2 were dispersed in 70 parts of the acrylic ester composite emulsion, and 7 parts of the surfactant polyethylene glycol sulfate were added dropwise to the mixed solution to obtain a porous adhesive.
[0037] Preparation Example 2
[0038] Preparation of porous adhesive
[0039] A1. Methyl methacrylate and triallyl isocyanurate are mixed in a mass ratio of 2:1 to form a polymer component, and then 50% of the mass of the polymer component of petroleum ether as a porogen and 1% of the mass of the initiator azobisisobutyronitrile as an initiator are added to the polymer component to obtain an oil phase, polyvinyl alcohol is mixed with water to form a 1% aqueous solution as the water phase, and the oil phase is added dropwise to the water phase, and the volume ratio of the oil phase to the water phase is 1:2, the temperature is raised to 60°C, and the reaction is carried out for 6 hours, and then the temperature is raised to 80 degrees Celsius and the reaction is carried out for 3 hours; 0.5BV of ethanol is used for soaking and impurity removal, and then 2BV of ethanol and hydrochloric acid are used for washing at a flow rate of 1BV / h for 2 hours, and finally sodium hydroxide solution is used for alkali washing, and water is washed until neutral to obtain a porous skeleton;
[0040] A2, formation of a porogen, dispersing 4,4-oxobisbenzenesulfonylhydrazine in a sodium hydroxide solution with a mass concentration of 10% to obtain a fluid, the solid-liquid ratio of 4,4-oxobisbenzenesulfonylhydrazine to the sodium hydroxide solution is 2.5 g / 100 mL, placing a porous skeleton in the fluid and stirring, the weight ratio of 4,4-oxobisbenzenesulfonylhydrazine to the porous skeleton is 0.6:1, adding hydrochloric acid to neutralize to neutrality and then standing for 2 hours, filtering to obtain a porogen, using low-temperature plasma to irradiate the porogen, using a low-temperature plasma treatment device with a radio frequency of 13.56 MHz and an output power of 300 W to irradiate for 3 minutes, and the gas medium is NH3, so that the surface of the porogen is activated;
[0041] A3, methyl methacrylate, butyl acrylate and glycidyl methacrylate were mixed in a molar ratio of 1:0.8:0.05, and stirred in deionized water to form an emulsion, and then an emulsifier sodium dodecyl sulfate and a pH regulator sodium bicarbonate were added with a molar number of 10% of methyl methacrylate, and ammonium persulfate with a molar number of 1% of methyl methacrylate was added dropwise, and the temperature was raised to 65°C for reaction for 3 hours, and then the temperature was raised to 85°C for standing for 2 hours, and then the pH was adjusted to neutral, and filtered after standing to obtain an acrylate composite emulsion;
[0042] Finally, 20 parts of the surface activated porogens in A2 were dispersed in 60 parts of the acrylic ester composite emulsion by weight, and 5 parts of the surfactant polyethylene glycol sulfate were added dropwise to the mixed solution to obtain a porous adhesive.
[0043] Preparation Example 3
[0044] Preparation of porous adhesive
[0045] A1. Methyl methacrylate and triallyl isocyanurate are mixed in a mass ratio of 4:1 to form a polymer component, and then 50% of the mass of the polymer component of petroleum ether as a porogen and 1% of the mass of the initiator azobisisobutyronitrile as an initiator are added to the polymer component to obtain an oil phase, polyvinyl alcohol is mixed with water to form a 1% aqueous solution as an aqueous phase, and the oil phase is added dropwise to the aqueous phase, and the volume ratio of the oil phase to the aqueous phase is 1:5, and the temperature is raised to 70°C, and the reaction is carried out for 6 hours, and then the temperature is raised to 80 degrees Celsius and the reaction is carried out for 3 hours; 0.5BV of ethanol is used for soaking and impurity removal, and then 2BV of ethanol and hydrochloric acid are used for washing at a flow rate of 1BV / h for 2 hours, and finally sodium hydroxide solution is used for alkali washing, and water is washed until neutral to obtain a porous skeleton;
[0046] A2, formation of a porogen, dispersing p-toluenesulfonyl hydrazide in a sodium hydroxide solution with a mass concentration of 10% to obtain a fluid, the solid-liquid ratio of p-toluenesulfonyl hydrazide to the sodium hydroxide solution is 2.5 g / 100 mL, placing a porous skeleton in the fluid and stirring, the weight ratio of p-toluenesulfonyl hydrazide to the porous skeleton is 1.4:1, adding hydrochloric acid to neutralize to neutrality and then standing for 2 hours, filtering to obtain a porogen, using low-temperature plasma to irradiate the porogen, using a low-temperature plasma treatment device with a radio frequency of 13.56 MHz and an output power of 300 W to irradiate for 3 minutes, and the gas medium is NH3, so that the surface of the porogen is activated;
[0047] A3, methyl methacrylate, butyl acrylate and glycidyl methacrylate were mixed in a molar ratio of 1:0.8:0.05, and stirred in deionized water to form an emulsion, and then an emulsifier sodium dodecyl sulfate and a pH regulator sodium bicarbonate were added with a molar number of 10% of methyl methacrylate, and ammonium persulfate with a molar number of 1% of methyl methacrylate was added dropwise, and the temperature was raised to 65°C for reaction for 3 hours, and then the temperature was raised to 85°C for standing for 2 hours, and then the pH was adjusted to neutral, and filtered after standing to obtain an acrylate composite emulsion;
[0048] Finally, 30 parts of the surface activated porogens in A2 were dispersed in 80 parts of the acrylic ester composite emulsion, and 10 parts of the surfactant polyethylene glycol sulfate were added dropwise to the mixed solution to obtain a porous adhesive.
[0049] Preparation Example 4: The porogen does not use a porous skeleton, but is coated with sodium alginate spheres
[0050] Preparation of porous adhesive
[0051] A1. Weigh sodium alginate and prepare a 5 wt% sodium alginate solution with hot water, and weigh calcium chloride solution to prepare a 4.0% (W / V) calcium chloride solution;
[0052] A2, p-toluenesulfonyl hydrazide was weighed and placed in a 75% ethanol solution to form an ethanol solution of 5.0 g / 100 mL, the sodium alginate solution and the ethanol solution of p-toluenesulfonyl hydrazide were mixed to obtain a coating solution, the mixing volume ratio was 1:1, and then the calcium chloride solution was added dropwise to the coating solution, and the mixture was spray-dried after being fully stirred to obtain colloidal particles embedded with p-toluenesulfonyl hydrazide, and the colloidal particles were irradiated with low-temperature plasma, and a low-temperature plasma treatment device with a radio frequency of 13.56 MHz and an output power of 300 W was used for irradiation for 3 min, and the gas medium was NH3, so that the surface of the colloidal particles was activated;
[0053] A3, methyl methacrylate, butyl acrylate and glycidyl methacrylate were mixed in a molar ratio of 1:0.8:0.05, and stirred in deionized water to form an emulsion, and then an emulsifier sodium dodecyl sulfate and a pH regulator sodium bicarbonate were added with a molar number of 10% of methyl methacrylate, and ammonium persulfate with a molar number of 1% of methyl methacrylate was added dropwise, and the temperature was raised to 65°C for reaction for 3 hours, and then the temperature was raised to 85°C for standing for 2 hours, and then the pH was adjusted to neutral, and filtered after standing to obtain an acrylate composite emulsion;
[0054] Finally, 25 parts of the surface activated colloidal particles in A2 were dispersed in 70 parts of the acrylic ester composite emulsion, and 5 parts of the surfactant polyethylene glycol sulfate were added dropwise to the mixed solution to obtain a porous adhesive.
[0055] Preparation Example 5: The foaming agent was not alkali-dissolved or acid-leached, but directly contacted and stirred
[0056] Preparation of porous adhesive
[0057] A1. Methyl methacrylate and triallyl isocyanurate are mixed in a mass ratio of 3:1 to form a polymer component, and then 50% of the mass of the polymer component of petroleum ether as a porogen and 1% of the mass of the initiator azobisisobutyronitrile as an initiator are added to the polymer component to obtain an oil phase, polyvinyl alcohol is mixed with water to form a 1% mass fraction aqueous solution as the water phase, and the oil phase is added dropwise to the water phase, and the volume ratio of the oil phase to the water phase is 1:3, the temperature is raised to 60°C, and the reaction is carried out for 6 hours, and then the temperature is raised to 80 degrees Celsius and the reaction is carried out for 3 hours; 0.5BV of ethanol is used for soaking and impurity removal, and then 2BV of ethanol and hydrochloric acid are used for washing at a flow rate of 1BV / h for 2 hours, and finally sodium hydroxide solution is used for alkali washing, and water is washed until neutral to obtain a porous skeleton;
[0058] A2, formation of porogens, dispersing p-toluenesulfonyl hydrazide in an ethanol solution to obtain a fluid, the solid-liquid ratio of p-toluenesulfonyl hydrazide to the ethanol solution is 2.5 g / 10 mL, then adding an appropriate amount of water to the ethanol solution of toluenesulfonyl hydrazide, and then placing a porous skeleton in the fluid and stirring, the weight ratio of p-toluenesulfonyl hydrazide to the porous skeleton is 1:1, and filtering to obtain a porogen after standing for 2 hours, irradiating the porogen with low-temperature plasma, using a low-temperature plasma treatment device with a radio frequency of 13.56 MHz and an output power of 300 W for irradiation for 3 minutes, and the gas medium is NH3, so that the surface of the porogen is activated;
[0059] A3, methyl methacrylate, butyl acrylate and glycidyl methacrylate were mixed in a molar ratio of 1:0.8:0.05, and stirred in deionized water to form an emulsion, and then an emulsifier sodium dodecyl sulfate and a pH regulator sodium bicarbonate were added with a molar number of 10% of methyl methacrylate, and ammonium persulfate with a molar number of 1% of methyl methacrylate was added dropwise, and the temperature was raised to 65°C for reaction for 3 hours, and then the temperature was raised to 85°C for standing for 2 hours, and then the pH was adjusted to neutral, and filtered after standing to obtain an acrylate composite emulsion;
[0060] Finally, 24 parts of the surface activated porogen in A2 were dispersed in 60 parts of the acrylic ester composite emulsion, and 6 parts of the surfactant polyethylene glycol sulfate were added dropwise to the mixed solution to obtain a porous adhesive.
[0061] Preparation Example 6—No Low-Temperature Plasma Irradiation
[0062] Preparation of porous adhesive
[0063] A1. Methyl methacrylate and triallyl isocyanurate are mixed in a mass ratio of 4:1 to form a polymer component, and then 50% of the mass of the polymer component of petroleum ether as a porogen and 1% of the mass of the polymer component of azobisisobutyronitrile as an initiator are added to the polymer component to obtain an oil phase, polyvinyl alcohol is mixed with water to form a 1% aqueous solution as the water phase, and the oil phase is added dropwise to the water phase, and the volume ratio of the oil phase to the water phase is 1:5, and the temperature is raised to 67°C, and the reaction is carried out for 6 hours, and then the temperature is raised to 80 degrees Celsius and the reaction is carried out for 3 hours; 0.5BV of ethanol is used for soaking and impurity removal, and then 2BV of ethanol and hydrochloric acid are used for washing at a flow rate of 1BV / h for 2 hours, and finally sodium hydroxide solution is used for alkali washing, and water is washed until neutral to obtain a porous skeleton;
[0064] A2, formation of porogen, p-toluenesulfonyl hydrazide is dispersed in a sodium hydroxide solution with a mass concentration of 10% to obtain a fluid, the solid-liquid ratio of p-toluenesulfonyl hydrazide to the sodium hydroxide solution is 2.5 g / 100 mL, a porous skeleton is placed in the fluid and stirred, the weight ratio of p-toluenesulfonyl hydrazide to the porous skeleton is 0.8:1, hydrochloric acid is added to neutralize to neutrality, and then allowed to stand for 2 hours, and filtered to obtain a porogen;
[0065] A3, methyl methacrylate, butyl acrylate and glycidyl methacrylate were mixed in a molar ratio of 1:0.8:0.05, and stirred in deionized water to form an emulsion, and then an emulsifier sodium dodecyl sulfate and a pH regulator sodium bicarbonate were added with a molar number of 10% of methyl methacrylate, and ammonium persulfate with a molar number of 1% of methyl methacrylate was added dropwise, and the temperature was raised to 65°C for reaction for 3 hours, and then the temperature was raised to 85°C for standing for 2 hours, and then the pH was adjusted to neutral, and filtered after standing to obtain an acrylate composite emulsion;
[0066] Finally, 30 parts of the surface activated porogens in A2 were dispersed in 70 parts of the acrylic ester composite emulsion by weight, and 10 parts of the surfactant polyethylene glycol sulfate were added dropwise to the mixed solution to obtain a porous adhesive.
[0067] Preparation Example 7 - No surfactant was added when the porogen was mixed with the acrylic ester composite emulsion
[0068] Preparation of porous adhesive
[0069] Finally, 25 parts of the surface activated porogen in A2 were dispersed in 75 parts of the acrylic ester composite emulsion, and 6 parts of the surfactant polyethylene glycol sulfate were added dropwise to the mixed solution to obtain a porous adhesive.
[0070] Example 1
[0071] A heat-insulating microfiber centrifugal glass wool thermal insulation material
[0072] S1, 80 parts of quartz sand, 30 parts of potassium feldspar, 20 parts of dolomite, 10 parts of limestone, 40 parts of borax, and 3 parts of soda ash were crushed into ore raw material powder and then mixed, 120 parts of ore raw material powder were weighed and mixed with 5 parts of calcium fluoride, and heated to 1420° C. to a molten state and kept for 15 minutes, and centrifugal spraying was performed to obtain glass fiber, and the speed of centrifugal spraying was 3700 rad / min;
[0073] The metal tin is placed in a 1 mol / L hydrochloric acid solution and after it is completely dissolved, polydimethylsiloxane is added dropwise to the acid solution of the metal tin to obtain a modified tin solution, wherein the weight ratio of polydimethylsiloxane to tin is 3:12;
[0074] The centrifugally sprayed and cooled glass fiber is immersed in modified tin solution, and ammonia water is added dropwise until white crystals stop precipitating. After standing, the glass fiber is filtered and dried, and then the glass fiber is placed in an environment of 550°C for 3 hours;
[0075] S2. Weigh the porous adhesive in Preparation Example 1, and evenly spray 45 parts by weight of the porous adhesive onto the surface of 55 parts by weight of modified fiber cotton by air spraying. After the cotton is shaped, heat it to 260° C. for pore formation and curing to obtain a glass wool thermal insulation material.
[0076] Example 2
[0077] A heat-insulating microfiber centrifugal glass wool thermal insulation material
[0078] S1, 80 parts of quartz sand, 20 parts of potassium feldspar, 30 parts of dolomite, 5 parts of limestone, 50 parts of borax, and 1 part of soda ash are crushed into ore raw material powder, 100 parts of ore raw material powder is mixed and ground with 3 parts of calcium fluoride, heated to 1360° C. to a molten state and maintained for 10 minutes, and centrifugal spraying is performed to obtain glass fiber, and the speed of centrifugal spraying is 3500 rad / min;
[0079] The metal tin is placed in a 1 mol / L hydrochloric acid solution and after it is completely dissolved, polydimethylsiloxane is added dropwise to the acid solution of the metal tin to obtain a modified tin solution, wherein the weight ratio of polydimethylsiloxane to tin is 2:12;
[0080] The centrifugally sprayed and cooled glass fiber is immersed in modified tin solution, and ammonia water is added dropwise until white crystals stop precipitating. After standing, the glass fiber is filtered and dried, and then the glass fiber is placed in an environment of 520°C for 1 hour;
[0081] S2. Weigh the porous adhesive in Preparation Example 2, and evenly spray 40 parts by weight of the porous adhesive onto the surface of 60 parts by weight of modified fiber cotton by air spraying. After the cotton is shaped, heat it to 230° C. to form holes and solidify it to obtain a glass wool thermal insulation material.
[0082] Example 3
[0083] A heat-insulating microfiber centrifugal glass wool thermal insulation material
[0084] S1, 80 parts of quartz sand, 40 parts of potassium feldspar, 10 parts of dolomite, 15 parts of limestone, 30 parts of borax, and 5 parts of soda ash are crushed into ore raw material powder, 140 parts of ore raw material powder is mixed and ground with 8 parts of calcium fluoride, heated to 1450° C. to a molten state and maintained for 20 minutes, and centrifugal spraying is performed to obtain glass fiber, and the speed of centrifugal spraying is 3900 rad / min;
[0085] The metal tin is placed in a 1 mol / L hydrochloric acid solution and after it is completely dissolved, polydimethylsiloxane is added dropwise to the acid solution of the metal tin to obtain a modified tin solution, wherein the weight ratio of polydimethylsiloxane to tin is 5:12;
[0086] The centrifugally sprayed and cooled glass fiber is immersed in modified tin solution, and ammonia water is added dropwise until white crystals stop precipitating. After standing, the glass fiber is filtered and dried, and then the glass fiber is placed in an environment of 580°C for 6 hours;
[0087] S2. Weigh the porous adhesive in Preparation Example 3, and evenly spray 55 parts by weight of the porous adhesive onto the surface of 45 parts by weight of modified fiber cotton by air spraying. After the cotton is shaped, heat it to 280° C. for pore formation and curing to obtain a glass wool thermal insulation material.
[0088] Comparative Example 1
[0089] A heat-insulating microfiber centrifugal glass wool thermal insulation material
[0090] The difference between this comparative example and Example 1 lies in the selection of the porous adhesive.
[0091] S2. Weigh the porous adhesive in Preparation Example 4, and evenly spray 45 parts by weight of the porous adhesive onto the surface of 55 parts by weight of modified fiber cotton by air spraying. After the cotton is shaped, heat it to 260° C. for pore formation and curing to obtain a glass wool thermal insulation material.
[0092] Comparative Example 2
[0093] A heat-insulating microfiber centrifugal glass wool thermal insulation material
[0094] The difference between this comparative example and Example 1 lies in the selection of the porous adhesive.
[0095] S2. Weigh the porous adhesive in Preparation Example 5, and evenly spray 45 parts by weight of the porous adhesive onto the surface of 55 parts by weight of modified fiber cotton by air spraying. After the cotton is shaped, heat it to 260° C. to form holes and solidify it to obtain a glass wool thermal insulation material.
[0096] Comparative Example 3
[0097] A heat-insulating microfiber centrifugal glass wool thermal insulation material
[0098] The difference between this comparative example and Example 1 lies in the selection of the porous adhesive.
[0099] S2. Weigh the porous adhesive in Preparation Example 6, and evenly spray 45 parts by weight of the porous adhesive onto the surface of 55 parts by weight of modified fiber cotton by air spraying. After the cotton is shaped, heat it to 260° C. for pore formation and curing to obtain a glass wool thermal insulation material.
[0100] Comparative Example 4
[0101] A heat-insulating microfiber centrifugal glass wool thermal insulation material
[0102] The difference between this comparative example and Example 1 lies in the selection of the porous adhesive.
[0103] S2. Weigh the porous adhesive in Preparation Example 7, and evenly spray 45 parts by weight of the porous adhesive onto the surface of 55 parts by weight of modified fiber cotton by air spraying. After the cotton is shaped, heat it to 260° C. to form holes and solidify it to obtain a glass wool thermal insulation material.
[0104] Comparative Example 5: No modification of the glass fiber surface using metallic tin
[0105] A heat-insulating microfiber centrifugal glass wool thermal insulation material
[0106] S1, 80 parts of quartz sand, 30 parts of potassium feldspar, 10 parts of dolomite, 15 parts of limestone, 40 parts of borax, and 3 parts of soda ash were crushed into ore raw material powder, 130 parts of ore raw material powder was mixed and ground with 6 parts of calcium fluoride, heated to 1380° C. to a molten state and maintained for 15 minutes, and centrifugal spraying was performed to obtain glass fiber, and the speed of centrifugal spraying was 3800 rad / min;
[0107] Adding polydimethylsiloxane to deionized water, with a solid-liquid ratio of polydimethylsiloxane to water being 15 g / 100 mL, to obtain a silane solution;
[0108] The centrifugally sprayed and cooled glass fiber is immersed in the silane solution, filtered and dried after standing, and then the glass fiber is placed in an environment of 540°C for 5 hours;
[0109] S2. Weigh the porous adhesive in Preparation Example 1, and evenly spray 50 parts by weight of the porous adhesive onto the surface of 50 parts by weight of modified fiber cotton by air spraying. After the cotton is shaped, heat it to 260° C. to form holes and solidify it to obtain a glass wool thermal insulation material.
[0110] Comparative Example 6 - No calcium fluoride was added to the ore raw material
[0111] A heat-insulating microfiber centrifugal glass wool thermal insulation material
[0112] S1, 80 parts of quartz sand, 30 parts of potassium feldspar, 20 parts of dolomite, 10 parts of limestone, 40 parts of borax, and 3 parts of soda ash were crushed into ore raw material powders and mixed, 120 parts of ore raw material powders were weighed and ground, heated to 1420° C. to a molten state and kept for 15 minutes, and centrifugal spraying was performed to obtain glass fiber, and the speed of centrifugal spraying was 3700 rad / min;
[0113] The remaining steps are the same as those in Example 1.
[0114] Experiments and data
[0115] The heat insulating microfiber centrifugal glass wool thermal insulation materials obtained from the above-mentioned Examples 1 to 3 and Comparative Examples 1 to 6 were subjected to performance tests, including thermal performance tests, glass wool tensile strength tests, and sound insulation performance tests.
[0116] Thermal conductivity: The thermal conductivity of glass wool at room temperature was tested using the German Netzsch HFM436 heat flow thermal conductivity analyzer, unit: mW / (m·K);
[0117] Tensile strength: Use a universal testing machine to test the tensile strength, unit: MPa;
[0118] Sound insulation performance: Use GB / T 18696.2-2002 test standard to obtain the thermal insulation coefficient;
[0119] The experimental data are shown in Table 1 and Table 2 below:
[0120] Table 1
[0121] Thermal conductivity Tensile Strength Example 1 19 46.8 Example 2 20 44.2 Example 3 21 45.7 Comparative Example 1 51 41.6 Comparative Example 2 37 43.7 Comparative Example 3 22 29 Comparative Example 4 44 38.6 Comparative Example 5 26 39.2 Comparative Example 6 23 40.3
[0122] The sound insulation test is performed at 1kHz, 3kHz, and 5kHz.
[0123] Table 2
[0124] Sound absorption coefficient Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 1kHz 0.87 0.83 0.85 0.52 0.77 0.86 0.81 0.84 0.85 3kHz 0.92 0.88 0.90 0.67 0.83 0.92 0.86 0.90 0.91 5kHz 0.97 0.94 0.95 0.82 0.89 0.95 0.91 0.95 0.93
[0125] Draw a bar graph of the above data, such as Figure 1 and Figure 2 shown.
[0126] analyze
[0127] It can be seen from the experimental data of Examples 1 to 3 that the thermal insulation microfiber centrifugal glass wool thermal insulation material prepared in the present application has a low thermal conductivity coefficient in terms of thermal conductivity, has a high resistance to heat conduction, can effectively keep warm, and has a high tensile strength, which proves that the use of tin oxide in the present application can greatly improve the tensile strength of glass fiber, and in the sound absorption test, the thermal insulation microfiber centrifugal glass wool thermal insulation material of the present application is far superior to other comparison examples and can achieve great absorption of sound waves.
[0128] It can be seen from the data of Comparative Example 1 that, compared with the embodiment, Comparative Example 1 has a higher thermal conductivity and better tensile strength, but a lower sound absorption coefficient. It can be seen that Comparative Example 1 does not use a porous skeleton to prepare the adhesive, which proves that the existence of the porous skeleton has a large energy level that affects the thermal conductivity of the glass wool, and the existence of porous channels has a greater effect on the absorption of sound waves.
[0129] It can be seen from the data of Comparative Example 2 that Comparative Example 2 did not perform the alkali dissolution and acid leaching operation, which had a greater impact on the combination of p-toluenesulfonyl hydrazide and the porous skeleton. Its thermal conductivity is high and the sound absorption coefficient is medium, which proves that the connected gaps do exist, but the number is small and cannot effectively weaken the sound waves, which proves that the p-toluenesulfonyl hydrazide content is low. This step operation can increase the content of p-toluenesulfonyl hydrazide in the porous skeleton.
[0130] It can be seen from the data of Comparative Example 3 that Comparative Example 3 was not irradiated with low-temperature plasma, and its thermal conductivity was relatively high, but its tensile strength was low. Since no activation was performed, the connection strength between the porous skeleton and the acrylic ester composite emulsion was low. Therefore, after subsequent heating and curing, the glass fiber and the porous skeleton were not only affected by the gap formed by the decomposition of p-toluenesulfonyl hydrazide, but also the strength of the connection through the acrylic ester composite emulsion was insufficient, resulting in a decrease in tensile strength. The sound absorption coefficient of Comparative Example 3 is high enough, so the sound insulation effect is good.
[0131] It can be seen from the data of Comparative Example 4 that no surfactant is added to Comparative Example 4. The experimental data show that its thermal conductivity is high, the tensile strength is medium, and the sound insulation effect is also at a medium level. Therefore, the surfactant has a certain effect on the dispersion of the porous skeleton, promotes the distribution of the porous skeleton in the composite emulsion, and can effectively increase the comprehensive performance of the glass wool.
[0132] It can be seen from the experimental data of Example 5 that Example 5 did not use metal tin to modify the surface of the glass fiber, so its thermal conductivity was slightly improved, the tensile strength was reduced, and the sound insulation performance was better, proving that the presence of metal tin can significantly improve the tensile strength of the glass wool.
[0133] It can be seen from the experimental data of Comparative Example 6 that no calcium fluoride is added to the ore raw material in Comparative Example 6, and its thermal conductivity is not greatly affected, the sound insulation performance is better, and the tensile strength decreases, which proves that the addition of calcium fluoride can enhance the strength of glass fiber.
[0134] So far, the technical solutions of the present invention have been described in conjunction with the preferred embodiments shown in the accompanying drawings. However, it is easy for those skilled in the art to understand that the protection scope of the present invention is obviously not limited to these specific embodiments. Without departing from the principle of the present invention, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will fall within the protection scope of the present invention.
Claims
1. A heat-insulating microfiber centrifugal glass wool thermal insulation material, characterized in that: The thermal insulation material is prepared by compounding 45-60 parts of modified fiber cotton and 40-55 parts of porous adhesive, wherein the modified fiber cotton is prepared by mixing 100-140 parts of ore raw materials and 3-8 parts of calcium fluoride, sintering the mixture, and then soaking the mixture in a modified tin liquid, wherein the modified fiber cotton is produced by a centrifugal blowing method, and the modified tin liquid is prepared by compounding hydrochloric acid, tin, and polydimethylsiloxane; The porous adhesive is composed of 20-30 parts by weight of porogen, 60-80 parts by weight of acrylic ester composite emulsion, and 5-10 parts by weight of surfactant. The preparation steps of the porous adhesive are as follows: A1, polymerization of the porous skeleton, mixing methyl methacrylate and triallyl isocyanurate, adding a porogen and an initiator to carry out polymerization reaction, and obtaining a porous skeleton; A2, formation of a porogen, dispersing p-toluenesulfonyl hydrazide or 4,4-oxobisbenzenesulfonyl hydrazide in an alkaline solution to obtain a fluid, placing a porous skeleton in the fluid and stirring, adding an acid solution to neutralize to neutrality and then standing, filtering to obtain a porogen, and irradiating the porogen with low-temperature plasma to activate the surface of the porogen; A3. Then, the porogen in A2 is dispersed in an acrylic ester composite emulsion, and a surfactant is added dropwise to obtain a porous adhesive.
2. The heat insulating microfiber centrifugal glass wool thermal insulation material according to claim 1, characterized in that: The weight ratio of the amount of p-toluenesulfonyl hydrazide or 4,4-oxobisbenzenesulfonyl hydrazide used in step A2 to the amount of the porous framework used is 0.6-1.4:1, the gas used in the low-temperature plasma is NH3, and the irradiation time is 3-5 minutes.
3. The heat insulating microfiber centrifugal glass wool thermal insulation material according to claim 1, characterized in that: The ore raw materials consist of 80 parts of quartz sand, 20-40 parts of potassium feldspar, 10-30 parts of dolomite, 5-15 parts of limestone, 30-50 parts of borax and 1-5 parts of soda ash.
4. The heat insulating microfiber centrifugal glass wool thermal insulation material according to claim 1, characterized in that: The polymerization reaction environment in step A1 is an aqueous phase dispersant, which is a polyvinyl alcohol solution, the polymerization temperature is 65-80°C, the polymerization time is 6-12h, and then 0.5BV of ethanol is used for soaking to remove impurities, followed by 2BV of ethanol and hydrochloric acid for 2h at a flow rate of 1BV / h, and then alkaline washing with sodium hydroxide solution, and washing with water until neutral to obtain a porous skeleton.
5. The heat insulating microfiber centrifugal glass wool thermal insulation material according to claim 1, characterized in that: The acrylic ester composite emulsion consists of methyl methacrylate, butyl acrylate, glycidyl methacrylate, an emulsifier and a pH regulator.
6. The heat insulating microfiber centrifugal glass wool thermal insulation material according to claim 5, characterized in that: The preparation steps of the acrylate composite emulsion are: emulsion polymerization of methyl methacrylate, butyl acrylate and glycidyl methacrylate to obtain the acrylate composite emulsion, the emulsifier is sodium dodecyl sulfate, and the pH regulator is sodium bicarbonate.
7. A method for preparing a heat insulating microfiber centrifugal glass wool thermal insulation material according to any one of claims 1 to 6, characterized in that: The specific preparation steps are as follows: S1. Mix and grind the ore raw material and calcium fluoride, heat to 1360-1450°C until molten state and keep for 10-20min, perform centrifugal spray coating to obtain glass fiber, soak the cooled glass fiber in modified tin liquid, add ammonia water dropwise until white crystals stop precipitating, let stand, filter and dry, and then place at 520-580°C for 1-6h; S2. The porous adhesive is evenly sprayed onto the surface of the modified fiber cotton by air spraying. After the cotton is shaped, it is heated to 230-280° C. for pore formation and curing to obtain a glass wool thermal insulation material.
8. The method for preparing a heat insulating microfiber centrifugal glass wool thermal insulation material according to claim 7, characterized in that: The modified tin solution is prepared by compounding hydrochloric acid, tin and polydimethylsiloxane, the concentration of the hydrochloric acid is 1 mol / L, and the weight ratio of the polydimethylsiloxane to the tin is 2-5:
12.
9. The method for preparing a heat insulating microfiber centrifugal glass wool thermal insulation material according to claim 7, characterized in that: The rotation speed of the centrifugal spraying in step S1 is 3500-3900 rad / min.
10. Use of the method for preparing a heat-insulating microfiber centrifugal glass wool thermal insulation material as claimed in any one of claims 7 to 9 in preparing building thermal insulation materials.
Citation Information
Patent Citations
Production method of flocculent glass wool
CN109020245A
Production method of microfiber glass wool for filtration
CN115893831A